A quality function deployment approach to improve maritime supply chain resilience. (August 2016) - Lam, Jasmine Siu Lee; Bai, Xiwen
Highlights: Quality function deployment approach can enhance maritime supply chain resilience. The model links customer requirements, maritime risk factors and resilience measures. Information technology, operational, and human resource management risks found influential. Top resilience measures are contingency plan, monitoring and maintenance, and supply chain relationship management. Abstract: Being international and involving numerous organizations as the basic nature, maritime supply chains are exposed to various natural and man-made risks. This paper aims to develop an original quality function deployment approach to enhance maritime supply chain resilience, taking both customer requirements and maritime risks into consideration. The empirical analysis is carried out through in-depth studies of three major shipping lines and their respective major shippers. The top three resilience measures are contingency plan, monitoring and maintenance, and supply chain relationship management. The study also unveils the relatively low visibility and integration in maritime supply chains.